Analysis of Disciplinary Characteristics of Elementary School Students: A Survey Research - Jaya, Fahira Pande; Magfhirah; Ariyati, Nisa (MANDAILING GLOBAL EDUKASIA, 2024)
This research aims to analyze the level of student discipline character in elementary schools at the Aceh Besar Regency level. This research uses a quantitative approach with a survey research type. The population of this study were elementary school students at the Aceh Besar Regency level with a research sample of 90 students from four different schools. The sampling technique used in this research was Cluster random sampling. This research data was collected using a questionnaire. The data obtained is quantitative data which was analyzed using descriptive statistical techniques. The results of this research show that students' disciplinary attitudes are fairly good, where the strategy carried out by the school to improve the formation of disciplinary character is the habit of activities that form disciplinary character. The habits include time discipline and how to dress. The implementation of school rules and regulations in improving the disciplinary character of elementary school students in Aceh Besar Regency has instilled a disciplinary character through religious activities and activities related to disciplinary character such as haircut rules, time discipline, Duha prayers. All these activities are carried out by the school through the habituation method. Student discipline in school grows because teachers provide motivation, create class rules, and reward students who are always on time.